The Comparative Efficacy of Multiple Interventions for Mild Cognitive Impairment in Alzheimer's Disease: A Bayesian Network Meta-Analysis - Lai, Xin; Wen, Hao; Li, Yu; Lu, Liming; Tang, Chunzhi (Frontiers in Aging Neuroscience, 2020)
Abstract: Background:Mild cognitive impairment(MCI) is the early phase of Alzheimer’s disease (AD).The early intervention of MCI to decrease the rate of conversion from MCI to AD is significant. However, the efficacy of multiple interventions in MCI and which way should be preferred are still matters of controversy. Consequently, we aimed to compare and rank the treatment methods for mild cognitive impairment (MCI)due to Alzheimer's Disease (AD),to find an optimal intervention of MCI and a way to prevent or delay the occurrence of AD. Methods:We did pair-wise meta-analysis and network meta-analysis to integrate the treatment effectiveness through direct and indirect evidence.Four English databases and three Chinese databases were searched for international registers of published and unpublished,eligible double or single blind,randomized controlled trials up to September 31, 2019.Compared nine comparative arms:pharmacological therapy:Cholinesterase inhibitors（ChEI）,Ginkgo, Nimodipine,Chinese Medicine;non-pharmacological therapy:Acupuncture,Music therapy,Exercise,Nutrition therapy;and placebo. The primary outcome was Mini-Mental State Examination(MMSE) ,The second outcome was AD Assessment Scalecognitive subscale (ADAS-cog). Results:We deemed 29 trials eligible, including 6957 participants.The overall effects of Music therapy (MD: 1.73 ; 95% CI: 0.30, 3.12) and Acupuncture(MD: 1.17; 95% CI: -0.80, 3.12) exerted significant therapeutic effect ;the overall effect of exercise showed a preference for MCI treatment (MD:0.53 ;95%CI:-1.09,2.21). Nutrition and Ginkgo treatment had the lowest rank among all interventions (-0.73,-1.93 to 0.51;-0.42,-2.30 to1.46 ). Conclusion:Among the nine treatments, The Music therapy had the highest probability to be the first best treatment of MCI, and Acupuncture had the second highest probability. Significant:Our study provide new ways of thinking to the clinical treatments of MCI due to AD,and may help the development of MCI guideline.